Pengaruh kebijakan dividen dan beban pajak tangguhan terhadap nilai perusahaan dengan return saham sebagai variabel moderasi - Pernita, Dita; Ismanto, Juli (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2025)
The purpose of this study is to analyze the effect of dividend policy and deferred tax burden on firm value and stock returns. For the years 2020–2023, this study aims to examine the determinants that influence changes in firm value in the Consumer Non-Cyclicals sector listed on the Indonesia Stock Exchange. A total of 10 companies were used as research samples over a four-year period, resulting in 40 data samples. For equations I and II, panel data regression analysis was used using a fixed effect regression model. Using the EViews13 program, a purposive sampling approach was used to test the hypothesis. The results showed that H1 Dividend Policy and Deferred Tax Burden both have an impact on firm value simultaneously, H2 Dividend Policy and H3 Deferred Tax Burden have no impact on firm value, and the MRA test showed that H4 Stock Returns cannot moderate the effect of Dividend Policy on Firm Value while H5 Stock Returns can moderate the effect of Deferred Tax Burden on Firm Value.